Microfinance impact on borrowers’ poverty in Bangladesh and Malaysia - Mohammad, Aslam (2021)
Poverty is a long standing issue that has been monitored as an economic, social, political and even moral problem around the globe. Microfinance has been designed to eliminate poverty through income-generating activities. The borrowers need money to materialize their dream and microfinance can play an important role. The poor have both intention and labor but they lack finance to start small enterprises. Through microfinance, small entrepreneurs may acquire necessary inputs to start their business. Both local governments and international agencies are trying to eliminate poverty through microfinance. This entrepreneurial concept may be able to generate new jobs and produce revenue that could eradicate poverty. With this concept, microfinance had been hosted primarily in Bangladesh and later replicated in Malaysia to alleviate poverty. Grameen Bank and BRAC are serving large number of borrowers below the poverty level in Bangladesh. Among others, TEKUN is serving the same purpose in Malaysia. Initially, microfinance institutions in both countries have been supported by the Government or Donor. However, both positive and negative impact on borrowers’ poverty have been visible in several studies that make microfinance still questionable. Therefore, this study measures microfinance impact on borrowers’ poverty at business, household, individual and security levels in Bangladesh and Malaysia. Both primary and secondary data are applied in this study. Primary data are gathered through a survey with the structured questionnaires while secondary data are taken from publicly available documents and websites. Microfinance impact on borrowers’ poverty has been measured through responses from participant and non-participant borrowers using Household Economic Portfolio Model (HEPM) for a quantitative perspective. The result shows positive impact within and between the participant and non-participant borrowers including casual impact using PLS-SEM. From a qualitative perspective, using Modified HEPM, positive impact on borrowers’ poverty has also been found through borrowers’ diaries. The incidence and intensity of poverty has been measured to compare participant borrowers with non-participant borrowers’ poverty by constructing the Multidimensional Poverty Index. This also showed positive impact on borrowers’ poverty. Furthermore, this study examined the microfinance loan default through Binomial Logistic Regression and found some significant determinants contributing to default. The social and financial performance of microfinance has been analyzed through panel data. As there was no mission drift except few indicators between social and financial performance, microfinance seems to contribute positively for poor borrowers. This research contributes by taking favorable position for microfinance debate academically. Its findings confirm microfinance industry dealing with huge investment and large number of borrowers contributing towards poverty alleviation. It also contributes through expanding quantitative measurement scope and adding qualitative aspect for microfinance impact on borrowers’ poverty in Bangladesh and Malaysia. Hence, policymakers need to continue and support microfinance as a development strategy.